2021
DOI: 10.3390/ijms221910522
|View full text |Cite
|
Sign up to set email alerts
|

Concepts in Oncolytic Adenovirus Therapy

Abstract: Oncolytic adenovirus therapy is gaining importance as a novel treatment option for the management of various cancers. Different concepts of modification within the adenovirus vector have been identified that define the mode of action against and the interaction with the tumour. Adenoviral vectors allow for genetic manipulations that restrict tumour specificity and also the expression of specific transgenes in order to support the anti-tumour effect. Additionally, replication of the virus and reinfection of nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(47 citation statements)
references
References 114 publications
0
44
0
3
Order By: Relevance
“…In contrast, cell viability experiments carried out on B16V and AB12 demonstrated that tested virus was able to infect and induce cell death in those cell lines, especially at a concentration of 100 VP/cell (cell viability was 40.4% and 44.7% for B16V and AB12, respectively) (Figure S1). This is not surprising as it is known that genetically modified adenovirus, delta-24, which has a 24-base pair deletion in the Rb-binding region of the E1A gene, shows selective replication and oncolysis in various malignant cells [37,38]. Expression level of adenovirus cell entry receptors on the surface of cancer cells show that the B16V and AB12 cell line expressed DSG2 receptors (approximately 21% and 98% of cells positive for the marker respectively).…”
Section: Resultsmentioning
confidence: 93%
“…In contrast, cell viability experiments carried out on B16V and AB12 demonstrated that tested virus was able to infect and induce cell death in those cell lines, especially at a concentration of 100 VP/cell (cell viability was 40.4% and 44.7% for B16V and AB12, respectively) (Figure S1). This is not surprising as it is known that genetically modified adenovirus, delta-24, which has a 24-base pair deletion in the Rb-binding region of the E1A gene, shows selective replication and oncolysis in various malignant cells [37,38]. Expression level of adenovirus cell entry receptors on the surface of cancer cells show that the B16V and AB12 cell line expressed DSG2 receptors (approximately 21% and 98% of cells positive for the marker respectively).…”
Section: Resultsmentioning
confidence: 93%
“…The xenograft models used in this manuscript also prove that in a 3-dimensional in vivo situation, the combination therapy used results in a much better oncolytic potency which corresponds to better replication compared to the virus monotherapy. However, for clinical purposes a humanized patient-derived xenograft model would be beneficial since the therapeutic effect of oncolytic viruses strongly depends on activating an anti-cancer immune response in vivo 56 .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, a maximum of three doses of ICOCAV15 were administered (one dog with one dose, five dogs with two doses, and two dogs with three doses). We believed it would be more effective, given that 90% of the virus had been eliminated intravenously within the first 24 h by elements of the immune system, and even if cell-mediated delivery is a way to avoid such elimination, there is still a risk of it occurring [ 45 , 46 ]. The patients included in the study were only those that had accessible tumors, to avoid administration-associated risks.…”
Section: Discussionmentioning
confidence: 99%